Melanotrichoblastoma: A Rare Case Report from B. P. Koirala Institute of Health Sciences, Dharan, Nepal - Pokharel, Sairil; Karki, S; Pradhan, A; Agrawal, S (Birat Journal of Health Sciences, 2017)
Melanotrichoblastoma is a variant of pigmented trichoblastoma. It shows heavily pigmented epithelial lobules and differentiaion toward the hair bulb. Abundant dendritic melanocytes are found within the tumor masses. These melanocytes show positivity for S100 protein, HMG45/gp 100 and tyrosinase. The case is being reported because of its rarity. A twenty eight year lady presented to Dermatology OPD with a single nodular lesion on the right temporal region since last five years. Punch biopsy was done. Haematoxylin and eosin stained slides were studied and immunohistochemistry analysis was also done. Variably sized epithelial lobules of basaloid cells spanning the entire dermis was noted on H and E stained slides. Some lobules showed pale looking cells- a reminiscent of follicular germinative cells. Intralesional melanocytes with pigmentation were observed. Immunohistochemistry results showed the melanocytes positive for HMB-45 and S100 and the stroma positive for CD 34. Hence, a definitive diagnosis of Melanotrichoblastoma was made. This case is being presented to emphasize the difficulty posed by adnexal tumors in clinical diagnosis due to their clinical similarity with malignant lesion and rarity. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017